DAYA HAMBAT CACING TANAH (Lumbricus rubellus) TERHADAP Salmonella typhi - Syarifah, Syarifah (Al 'Ilmi : Jurnal Pendidikan MIPA, 2012)
Soil  worms (Lumbricus rubellus) are widely used as traditional medicine for thypus or thyphoid fever, because it is easily got and easy to use. Usage the soil ucages is boiled and it’s water is used for tratment, beside it can be used in power form and the pathaged in capsules can also be in the form of extracts. The poupose of study was to determine the inbibition zona  of soil worms (Lumbricus rubellus) to the growth of Salmonella typhy. The riset war dine in BBLK( (balai Besar Laboratothim Kesehatirn) from June-july 2011. The type of study war pre-eksperimental The sample was 1000 gram soil worms. The soil worm (Lumbricus rubellus) war hoped can be used as a traditional medicine to inhibit the growth Salmonella typhy The method used was kirby bauer. The prirniple of examinination war to use varius concentrations of soil worms (Lumbricus rubellus)from 10% - 50% concentrate to inhibit the growth of  Salmonella typhy The resuls showed minimum diamets of inhibition zona was 9 mm for 20% concentration  and maxunum diamets was 18 mm for 50% concentrate. Therfor it is hoped that people use soil worm (Lumbricus rubellus) as a drug for typhus (typhoid fever).